Measuring Value Added in Gross Trade: Endogenous Approach of Vertical Differentiation - Sourish Dutta (ZBW – Leibniz Information Centre for Economics, 2023)
From the beginning of the 1980s, the first theoretical analysis of intra-industry trade showed that the determinants and consequences of this type of trade are different, depending on whether the traded products differ in quality. When the products are subject to intra-industry trade between two countries with distinct qualities, this trade is vertically differentiated. Otherwise, it is called horizontal differentiation. There is a method for distinguishing intra-industry trade between two countries in vertical differentiation from those in horizontal differentiation. This method compares exports' unit value to imports for each industry's intra-industry trade. It considers the intra-industry trading carried out in this industry as vertical differentiation when the unit value of exports differs significantly from that of imports. This approach has limitations. The discussion below will lead us to think about an alternative method for separating and measuring intra-industry trade into horizontal and vertical differentiation.
Keywords: F0; F1; 330; Intra-industry Trade; Vertical Intra-industry Trade; Horizontal Intra-industry Trade; Value Added